$(L^p,L^q)$-Boundedness of Hausdorff Operators with Power Weight on Euclidean Spaces (Analysis in Theory and Applications, 2017)
In this paper, we prove the $(L^p, L^q)$-boundedness of (fractional) Hausdorff operators with power weight on Euclidean spaces. As special cases, we can obtain some well known results about Hardy operators.